Linear scleroderma and primary sclerosing cholangitis: An undescribed association - Iñigo Navarro Fernández; Susana Armesto Alonso; Carlos Duran Vian; L Reguero Del Cura; Carmen González-Vela; Marcos González-López (Wolters Kluwer Medknow Publications, 2020)
Linear scleroderma (LS) is clinically characterized by the presence of sclerotic areas of skin, which develop in a linear pattern. Primary sclerosing cholangitis is a cholestatic disorder that can lead to end-stage liver disease. We present, for the first time in English literature, the case of a patient suffering from both the diseases. This highlights the fact that, even though LS has conventionally been considered to be a form of localized scleroderma, this does not necessarily imply that it is an exclusively cutaneous disease.